Home appliances get smart. - Badami, V.V (IEEE spectrum)
The authors describe how novel sensors and control algorithms embedded in today's domestic appliances make them smart enough to estimate the size and dirtiness of a load of clothes tossed in a washer or to determine whether water in a pot on the stove is boiling. They argue that, as semiconductor costs come down, such appliances will get even smarter